-3(t+5)+(4t+20)=8

Simple and best practice solution for -3(t+5)+(4t+20)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(t+5)+(4t+20)=8 equation:


Simplifying
-3(t + 5) + (4t + 20) = 8

Reorder the terms:
-3(5 + t) + (4t + 20) = 8
(5 * -3 + t * -3) + (4t + 20) = 8
(-15 + -3t) + (4t + 20) = 8

Reorder the terms:
-15 + -3t + (20 + 4t) = 8

Remove parenthesis around (20 + 4t)
-15 + -3t + 20 + 4t = 8

Reorder the terms:
-15 + 20 + -3t + 4t = 8

Combine like terms: -15 + 20 = 5
5 + -3t + 4t = 8

Combine like terms: -3t + 4t = 1t
5 + 1t = 8

Solving
5 + 1t = 8

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 1t = 8 + -5

Combine like terms: 5 + -5 = 0
0 + 1t = 8 + -5
1t = 8 + -5

Combine like terms: 8 + -5 = 3
1t = 3

Divide each side by '1'.
t = 3

Simplifying
t = 3

See similar equations:

| 86+5x=8x-28 | | 6+(-1)= | | 5(5g+4)=17.5/4 | | 5(5g+4)=17.5 | | 13d+3=5d+35 | | 9k+6=k+13 | | 7x^3+6x+19=2x^2 | | 91-7x=11x+23 | | -164-10x=10+16 | | 3x+28=6x-32 | | 4(2x+1)+3(x-5)=0 | | 10x+5=8+17 | | -5+11=13x-3-12x | | 8x^2+4x-85=0 | | 6(x-5)=78*13 | | y=5x/6+2 | | 1/2x+6=x-1 | | x^2+x/2-9=0 | | x*4x=3300 | | x*4y=3300 | | 4y^2+12x=36+x^2 | | t-34=-35 | | 3-3u/7=9 | | 24=1750(19/36) | | 24=1750(19/36) | | -3(7-y)-6=-18 | | 5z=3z+8 | | 40=80/x+x | | 4(x+3)+5=17 | | 3x-6=2(x+2) | | 3-x=35 | | 115-5x=6x+23 |

Equations solver categories